Service Quality Status and Customer Satisfaction in Commercial Banking Sector of Nepal - Thapa, Makshindra (The Batuk, 2020)
The basic intent of this study is to reveal existing level of service quality of some Nepalese commercial banks. The customer perception to measure bank services quality within five dimensions; tangibles, reliability, responsiveness, assurance and empathy are considered as to service quality model introduced by Parashuranman et. al. in 1988. This study is a descriptive in nature and uses primary data collected through personally administered questionnaire survey with customers of some selected commercial banks including public and private banks. The questionnaire includes 22 questions in total for five dimensions. The sample size of the study is 82 respondents of the banks selected on convenience basis. The analysis consist descriptive statistics and t-test in order to meet the study objectives.